1-Month Relapse of Undifferentiated Sarcoma in the Left Atrium - Isabella Fumarulo, MD; Massimiliano Camilli, MD; Irma Bisceglia, MD; Massimo Massetti, MD; Antonella Lombardo, MD; Nadia Aspromonte, MD (JACC: Case Reports)
Primary cardiac sarcomas are extremely rare. Echocardiography provides initial information about tumor location and size. However, due to the frequent resemblance to benign myxomas or thrombotic formations, the correct diagnosis often requires a multimodal approach. We report a case of undifferentiated cardiac sarcoma in a 46-year-old woman who underwent surgical resection. One month after the operation, echocardiography revealed disease recurrence. The patient underwent chemotherapy and hypofractionated radiotherapy with significant reduction of mass size. Primary cardiac sarcomas may be suspected by multimodality imaging tests, but the definitive diagnosis is histologic. There is still no international agreement about imaging criteria to define these tumors or optimal treatment. Radical surgery is potentially the best therapeutic option, but it is still burdened by high recurrence rates; radiotherapy, chemotherapy and immunotherapy appear promising, especially when used in combination.